Pemetaan Potensi Ekonomi di Pulau Jawa Berdasarkan Pendekatan LQ, DLQ, dan Analisis Input-Output - Khoirotun Ni’mah; Nurjannah Rahayu Kistanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Java contributes 57.04% of the national GDP, making it the primary engine of Indonesia’s economic growth. However, the six provinces receive this contribution unevenly, with pronounced disparities between northern and southern Java. Through Presidential Regulation No. 72 of 2023, the government has designated Main Activity Centers (PKU) and Supporting Activity Centers (PKP) on the island to promote more balanced economic development. However, the economic roles assigned to each PKU remain broad, and no recent study has mapped Java’s leading sectors to inform more targeted, potential-driven planning. Therefore, this research applies Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Input-Output Table Analysis—Backward Linkage (IBL) and Forward Linkage (IFL)—to identify each province’s core sectors and their linkages. The results show that according to LQ and DLQ, Java’s leading sectors are wholesale and retail trade, construction, manufacturing, and education services; meanwhile, IBL and IFL analyses reveal that electricity and gas procurement, along with wholesale and retail trade, dominate in almost all provinces. These findings are expected to provide an initial framework for economic development planning aligned with each province’s economic structure, ensuring policies are optimally implemented.